1986
DOI: 10.1159/000124667
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Blood Levels of Androgens in Female Talapoin Monkeys Related to Their Social Status

Abstract: Serum testosterone and androstenedione levels were lower in the subordinate female talapoin monkeys of four social groups than either dominant or intermediate-ranking females. This was found in both intact or ovariectomized (oestrogen-treated) animals, which suggests that androgen from the adrenals contributed to this rank-related endocrine effect. These differences disappeared when the females were housed singly, levels in all animals becoming similar to those in subordinates in the group cage. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
(27 reference statements)
2
12
2
Order By: Relevance
“…(c) Only the rank indices and not the androgen concentrations were correlated with the relative testis size (stepwise forward multiple regression, rank index bˆ0.25 § 0.08 and p 5 0.05, and androgen concentration bˆ0.00 § 0.00 and n.s.). Bouissou 1983a,b;Floody 1983) and that high-ranking females can have higher androgen concentrations (Batty et al 1986;Faulkes & Abbott 1997) suggested that female dominance in lemurs may be associated with increased levels of testosterone or other androgens. Even though the ranges of androgen levels in female ring-tailed lemurs appear high in relation to male levels (cf.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Only the rank indices and not the androgen concentrations were correlated with the relative testis size (stepwise forward multiple regression, rank index bˆ0.25 § 0.08 and p 5 0.05, and androgen concentration bˆ0.00 § 0.00 and n.s.). Bouissou 1983a,b;Floody 1983) and that high-ranking females can have higher androgen concentrations (Batty et al 1986;Faulkes & Abbott 1997) suggested that female dominance in lemurs may be associated with increased levels of testosterone or other androgens. Even though the ranges of androgen levels in female ring-tailed lemurs appear high in relation to male levels (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of sexual dimorphism involves talapoin monkeys (Miopithecus talapoin). Dominant females have higher circulating cortisol concentrations and engage in more aggressive interactions than subordinate females [37]. However, when individually housed, previously dominant and subordinate female monkeys have similar blood cortisol concentrations, which suggests that elevated cortisol concentrations in dominant females are observed only in a social context [37].…”
Section: Sexmentioning
confidence: 99%
“…Dominant females have higher circulating cortisol concentrations and engage in more aggressive interactions than subordinate females [37]. However, when individually housed, previously dominant and subordinate female monkeys have similar blood cortisol concentrations, which suggests that elevated cortisol concentrations in dominant females are observed only in a social context [37]. In male talapoin monkeys, cortisol concentration is correlated with dominance rank, but it is the subordinate monkeys that receive the majority of the aggressive attacks and have the highest cortisol concentrations [38].…”
Section: Sexmentioning
confidence: 99%
“…Such females, for example, start to cycle immediately (Abbott et al 1988). As the androgen levels of male and female NHPs were shown to be linked also to behavioural traits that influence social rank (Batty et al 1986, Ross et al 2004, it might be that, specifically in the marmoset, androgens play a minor role in the regulation of the reproductive organs but are of higher importance for maintenance of social status compared with other primate species. This assumption could explain why we observed complete spermatogenesis and maintained fertility in the treated males, although serum testosterone as well as pituitary CG responded to the TU/NETE treatment largely as expected.…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 99%